Sur les traces de John MacCrae, ou l’inscription dans l’espace public du souvenir d’un combattant de 1914-1918 - Emmanuelle Danchin (Revue LISA)
John MacCrae (1872-1918) enlisted in the Canadian Army Medical Corps as a physician in 1914. He was indirectly responsible for the decision by Commonwealth countries in 1921 to adopt the poppy as a symbol to commemorate the fallen of the Great War. He was buried in Wimereux, a small town in northern France. Starting from the example of Wimereux, we shall consider what remains of his life and memory. Can Wimereux be considered as a place of remembrance or a place of commemoration ? What traces remain today of his presence ? How long has MacCrae been commemorated and where is this tribute paid ? Who is really being honoured ? To what extent is Wimereux different from the other places devoted to his memory ?Considering the example of MacCrae will also enable us to reflect on both material and immaterial (internet) traces of memory and on how the circulation of iconic images leaves traces over time in public spaces. Indeed what matters most is not so much John MacCrae himself, but what he left behind and what this tells us today about this conflict nearly 100 years ago.